The Discourse of La Nación Newspaper about the Political Participation of Young People in Costa Rica (2009-2014) (Revista Rupturas, 2016)
This paper tries to determine the images of the young people that are shown in the articles published in La Nación. For this purpose newspaper articles concerning four different situations were collected. The situations chosen for this study were: the marches of May 1st (2009-2014), Movement for "Photocopying Act" (2012), the implementation of sex education in public high schools (2013) and the national election process (2013-2014). The analysis of the articles led to the visualization of differences in La Nación's discourse regarding the participation of young people. Different discourses found depend on the space -institutionalized or not institutionalized -in which young people participation occurs. The paper also tries to identify adult-centered elements present in the discourse of this newspaper.
Keywords: Discourse analysis; political participation; youth; media; Costa Rica